The Corporate governance and its role in protecting the rights of investors "Analytical Study" - KHUDHAIR ABBAS AIKHAMEES, YAS; NEAMAH ABDULRAZZAQ, DIANA; NIHRO JABAL, SHAYMAA (International Journal of Psychosocial Rehabilitation, 2020)
The research aims to study and analyze the role of governance in achieving the necessary protection to ensure the rights of shareholders. The corporate governance and the obligation of companies to implement them, which weakens the possibility of protecting the rights of shareholders and investors in The study applied to a sample of (42) special questionnaires in the analysis and represents (84%) of the total questionnaires distributed to investors and shareholders in all companies listed on the Iraqi market for securities, and the research concluded that the right of shareholders to obtain methods securing the registration, transfer and transfer of ownership of shares, as well as obtaining timely and material information relevant to the company and on a regular basis, The Board of Directors, the right to participate in the decisions as well as to obtain information resulting from the decisions concerning the amendment of the rules of procedure, the memorandum of association or the issuance of additional shares, or all that leads to the sale of the company, the most important recommendation of the company is necessary to the necessary Beneficiaries.